Love redesigned eaudiobook A sweet romantic comedy. - Proctor, Jenny (Some Kind of Love, 2021)
A Wedding dress heist with my ex? Why not? Going home to my twin brother's house in Charleston with my tail between my legs is the last thing I want to do. But when I walk out on my fashion house dream job, I don't exactly have a choice. Living in New York City is anything but free. But going back to Charleston...Alex is in Charleston. And facing down my ex? My ex who just happens to be stepson to my former boss? Even my love for Southern humidity and shrimp and grits can't make that confrontation worth it. There's just so much that could go wrong. The thing is, I need Alex's help to steal back a wedding dress, an original creation designed by yours truly, that my conniving boss stole out from under me. If I'm going to make it happen, Alex is my ticket. Stealing a wedding dress from a high-profile wedding? No problem. Accepting I'm still in love with my ex? Well, that's another matter entirely. Love Redesigned is a second-chance closed-door romance with sizzling kisses, secondary characters you'll love, and a happily-ever-after you won't expect. Books in the Some Kind of Love series are connected but can be read in any order.